Transposição didática interna : as transformações adaptativas realizadas sobre o saber matemático função afim para o ensino na Educação de Jovens e Adultos - Pantoja, Lígia Françoise Lemos (2017)
In this research invaestigates the didactic transposition process on the know internal mathematician function order when taught in education of young and adults-eya. The focus of analysis is the transformation process that occurs between know to be taught present in textbook and what professor effectively teaches in class in view of the needs of the public to which intended the teaching of referred to in mathematician, know case, the EYA. For this, we seek support in Transposition Didactic, studying the transformations held on a know to make it in education object context classroom, and in theory of Didactic, Anthropological as a analysis method that allows the existing praxeologias look within a certain institution, as the textbook and professor, for example. The research was held in two stages: the first we have reviewed as mathematical and didactics organisations present in textbooks used as reference for the teaching of function order in a class of EJA and, in the second, we follow the classes developed by professor of class analyzing also their mathematical and didatic organizations with the intention to visualize the transformations adaptive held on the know teaching. In nature analysis on the praxiological held textbooks used as know of reference for teaching, we note that the contents of affine function order was quite explored and approached via the presentation of situations involving contexts of daily life and mathematician, with a number task whose expressive techniques resolution presented were used as parameter to the coping complementary task. Already, in teaching praxeology analysis, we note that only part of function order content was worked, being the same developed through the presentation of tasks that involved everyday of contexts of students EYA with emphasis on presentation of diversified resolution techniques, but without a concern with formal of knowledge taught. In the development of teaching praxeology some modifications were held on the know teaching that ended up reveal some evidence of educational needs of EYA students, including the that need: study significant and claim content through interconnection between knowledge; have their knowledge accumulated respected and used in the process of teaching and learning; assist methodologies that in the construction of knowledge, in particular, study the knowledge coping with emphasis on and not task in the presentation significant little content; space for dialogue and interact. Such needs need attention and should be considered by the institutions, especially by textbook authors, with a view to training of students EYA amid their specifics.